2013
DOI: 10.3389/fneur.2013.00010
|View full text |Cite
|
Sign up to set email alerts
|

How Does Fingolimod (Gilenya®) Fit in the Treatment Algorithm for Highly Active Relapsing-Remitting Multiple Sclerosis?

Abstract: Multiple sclerosis (MS) is a neurological disorder characterized by inflammatory demyelination and neurodegeneration in the central nervous system. Until recently, disease-modifying treatment was based on agents requiring parenteral delivery, thus limiting long-term compliance. Basic treatments such as beta-interferon provide only moderate efficacy, and although therapies for second-line treatment and highly active MS are more effective, they are associated with potentially severe side effects. Fingolimod (Gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…6,7 Three landmark phase 3 clinical trials [8][9][10] In the TRANSFORMS study, all patients experienced relapses before randomization, but approximately 45% of the participants were treatment naive. The active comparator to fingolimod in that study was 30 μg of intramuscular interferon beta-1a, which had been shown to be inferior to 44 μg of subcutaneous interferon beta-1a 11 or glatiramer acetate.…”
mentioning
confidence: 99%
“…6,7 Three landmark phase 3 clinical trials [8][9][10] In the TRANSFORMS study, all patients experienced relapses before randomization, but approximately 45% of the participants were treatment naive. The active comparator to fingolimod in that study was 30 μg of intramuscular interferon beta-1a, which had been shown to be inferior to 44 μg of subcutaneous interferon beta-1a 11 or glatiramer acetate.…”
mentioning
confidence: 99%
“…146 147 In relapsing multiple sclerosis, early attack rate is associated with long term outcomes. 38 140 Several definitions of "highly active" or "aggressive" disease have been proposed for clinical use, [143][144][145][146][147][148][149] or to facilitate subgroup analyses of RCT data, [150][151][152] typically using a combination of two or more clinical relapses together with one or more of relapse severity, presence of multiple gadolinium enhancing MRI lesions, significant T2 lesion burden, or increase in EDSS score within the preceding year.…”
Section: Individual Disability Risk Stratificationmentioning
confidence: 99%
“…Adjusted Cox proportional regression analyses showed that patient group was not independently predictive of time to first relapse (IFN-b/GA-fingolimod HR 5 1. 26 figure 3A). Our analysis had 90% power at the level of a 5 0.05 to detect a difference between groups of 4.7% and 3.3%, respectively, relative to the naive-fingolimod group.…”
mentioning
confidence: 92%
“…There are currently no guidelines for the optimal period between natalizumab cessation and fingolimod start, but a period of 3 to 6 months has frequently been recommended. 26,27 Moreover, in certain countries, including Italy, a minimum 3-month washout period is mandated before fingolimod treatment can begin, whereas in other countries, such as Australia, there is a degree of flexibility and a period of 8 weeks washout is often used. Our data suggest that a treatment gap of 2-4 months was an independent predictor of increased relapse risk on fingolimod vs no treatment gap, whereas a treatment gap of 1 day to 2 months was not.…”
mentioning
confidence: 99%